A theoretical study on the dynamics of light harvesting in the dimeric photosystem II core complex: regulation and robustness of energy transfer pathways. (24th April 2019) - Hsieh, Shou-Ting; Zhang, Lu; Ye, De-Wei; Huang, Xuhui; Cheng, Yuan-Chung
Abstract : Coarse-grained model for dimeric PSII core complex reveals robust light harvesting through inter-monomer energy transfer and pooling in CP47s. Abstract : Here we present our theoretical investigations into the light reaction in the dimeric photosystem II (PSII) core complex. An effective model for excitation energy transfer (EET) and primary charge separation (CS) in the PSII core complex was developed, with model parameters constructed based on molecular dynamics (MD) simulation data. Compared to experimental results, we demonstrated that this model faithfully reproduces the absorption spectra of the RC and core light-harvesting complexes (CP43 and CP47) as well as the full EET dynamics among the chromophores in the PSII core complex. We then applied master equation simulations and network analysis to investigate detailed EET plus CS dynamics in the system, allowing us to identify key EET pathways and produce a coarse-grained cluster model for the light reaction in the dimeric PSII core complex. We show that non-equilibrium energy transfer channels play important roles in the efficient light harvesting process and that multiple EET pathways exist between subunits of PSII to ensure the robustness of light harvesting in the system. Furthermore, we revealed that inter-monomer energy transfer dominated by the coupling between the two CLA625 molecules enables efficient energy exchange between two CP47s in the dimeric PSII core complex, which leads to significant energy pooling in the CP47 domain during the light reaction. Our study provides a blueprint for the design of light harvesting in the PSII core and show that a structure-based approach using molecular dynamics simulations and quantum chemistry calculations can be effectively utilized to elucidate the dynamics of light harvesting in complex photosynthetic systems.